Design and Implementation of Scientific Inquiry using Technology in a Teacher Education Program - Sheffield, Rachel; McIlvenny, L. (Institute for Innovation in Science and Mathematics Education, 2014)
Two hundred and fifteen pre-service teachers engaged in a scientific inquiry unit in the newly created Bachelorof Primary and Early Childhood Education course at an Australian university This paper discusses how theTechnological, Pedagogical and Content Knowledge (TPACK) model provided the conceptual framework todesign an online inquiry unit. The unit enabled students to research an authentic problem focusing onenvironmental sustainability using an inquiry framework and an array of information and communicationtechnology (ICT) tools. The survey data collected at the conclusion of the unit indicated that 90 % of studentsthought the unit improved their understanding of the inquiry process and 88% reported more confidence in theirunderstanding of science concepts. Ninety four percent of students reported an increase in their knowledge andconfidence of Web 2.0 tools in supporting scientific inquiry in science. The research determined that the onlinescaffolded inquiry improved students’ knowledge and confidence in the skills and processes associated withinquiry and in science concepts. It will, however, not replace more traditional hands-on investigative approachesbut provides a complementary valuable tool to teach interesting and engaging science.